SUPPLY CHAIN SECURITY (Perner's Contacts, 2013)
Supply chain security is a vital topic in today's globalized world. Risks and threatsto the supply chains affect business interests of involved stakeholders includingcustomers. The paper discusses supply chain security dilemma with focus on supplychain security programs and initiatives as well as on mutual recognition programswithin a business partnership.
Keywords: supply chain; mutual recognition; security; security programs